The Effect of Cash Turnover, Account Receivable Turnover and Inventory Turnover on ROA in Mining and Quarrying Sector Companies Listed in IDX From 2017-2019 - Heliani Lismana; Risma Yulianti; Vina Herdina; Fitri Mareta; Indah Purnamasari (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2021)
ABSTRACT. The mining sector is a manufacturing company sector whose activities consist of extracting, processing and exploiting and selling coal, minerals, metals and natural gas. This research was conducted with the aim to determine whether ROA is affected by cash turnover, accounts receivable turnover and inventory turnover using documentation as a data collection and a method of multiple linear regression analysis through SPSS data processing. The population used is the mining and quarrying sector companies listed on Indonesia Stock Exchange (IDX) from 2017-2019 totaling 43 companies. The purposive sampling method was used in determining the sample which resulted in 33 samples. The research shows that cash turnover, accounts receivable turnover and inventory turnover have no effect on ROA because this is due to a decrease in the amount of production, cash flow constraints due to low turnover of accounts receivable and low sales so that inventory turnover is slow and inventory costs are higher.